Elementary School Teacher Performance Improvement Strategy in Supporting Quality Education - Frisila, Milinia; Niron, Maria Dominika (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
The challenges in realizing quality education in Indonesia are still significant. One of the main challenges is the inequality of education quality in various regions, especially in areas that are classified as remote or with limited resources. This study aims to analyze the strategies of school principals in improving teacher performance using a qualitative approach based on case studies. The subjects of the study included school principals and teachers. Data were collected through interviews, observations, and documentation, then analyzed in three stages: data condensation, data presentation, and drawing conclusions and verification. Data condensation was carried out by summarizing and sorting relevant information, while data presentation was in the form of narratives, tables, or diagrams to highlight the principal's supervision policies. Conclusions were drawn based on the patterns found and verified to ensure their validity. The results of the study showed that teachers have competence in learning planning, mastery of material, and implementation of strategies and evaluation. School principals play a strategic role in improving the quality of teaching through the provision of facilities, motivation, training, and strengthening collaboration with teachers and other stakeholders. This study implies that school principals can guide, supervise, and provide appreciation to teachers in order to improve the quality of education in schools.